Sharia Compliance Contracts Of Muamalat Bank Fund Distribution Products - Ninda Ardiani; Meri Yuliani; Masruchin (Perisai : Islamic Banking and Finance Journal, 2022)
This study is intended to determine the Aqad Sharia Compilance product distribution of Islamic bank funds. This level will show how Islamic banks carry out the tijarah function and the tabarru function together to create the value of the existence of falah or welfare. Approach The research uses a case study approach. The results showed that Bank Muamalat Mas Mansyur Surabaya branch office had level one Sharia Aqad Compliance on fund distribution products with the dominance of murbahah contracts. However, bank Muamalat is in an effort to reach the 4th level of Aqad Syariah Compliance to maximize the distribution of Musyarkah financing in the spiritual market. Unfavorable economic conditions as well as for mitigating risks that may arise have made the Sharia Aqad Compliance Level for distribution products at level one. This shows that Muamalat bank has not been optimal in carrying out the tabbaru function properly. However, Bank Muamalat has a positive value from their market share priority which is targeting the spiritual market. Giving priority to the spiritual market indicates that Bank Muamalat is not only looking for profit but is trying to balance the value of their kaffah.